Effect of ash preparation method on the sintering characteristics of ashes from combustion of coal and biomass blends. (15th December 2016) - Jing, Nijie; Zhu, Mingming; Shen, Guoqing; Wang, Qinhui; Zhang, Dongke
Highlights: Effect of ash preparation methods on ash sintering systematically studied. Sintering temperatures were lowest for low temperature ashes. Sintering temperatures were highest for high temperature ashes. Biomass addition in coal significantly reduced ash sintering temperature. K- and Ca-bearing minerals played a key role in determining sintering temperatures. Abstract: Sintering behaviour of ashes from combustion of coal and biomass blends was experimentally investigated with a focus on the effect of ash preparation method. Blends of a Chinese anthracite, Jincheng coal, and two biomass materials, a wheat straw and a pine sawdust, respectively, were subjected to three different ash preparation procedures, namely, a low temperature oxygen plasma ashing device operating at ca 150 °C, combustion in a Muffle furnace at 815 °C and in a drop tube furnace at 1500 °C. The resulting ash samples were then subjected to the sintering temperature measurement using a pressure-drop sintering device, morphological and mineralogical characterisation using scanning electron microscope (SEM) fitted with X-ray energy dispersive spectroscopy (EDS) and X-ray diffractometry analyser (XRD), respectively. For the same coal and biomass blends but different ash preparation methods, the sintering temperatures were always the lowest for the ash samples from the plasma ashing device and the highest from drop tube furnace. SEM imaging showed that the texture of ash samples from the plasma ashing device was irregular, loose and more fibrous, indicating little interactions among the different mineral and inorganic constituents in the individual fuels. The muffle furnace and drop tube furnace ashes were denser and more uniform in shape as the mineral matter and inorganics became fused together. In addition, the drop tube furnace ashes were mostly in spherical-shape, indicating ash melting had occurred during combustion. The XRD analysis revealed that different minerals were present in the ash samples due to different ash preparation temperatures, with high temperature minerals present in the drop tube furnace ash. Biomass addition in the blends lowered the sintering temperature of corresponding ash; the higher the proportion of biomass in the blend, the lower the ash sintering temperature regardless the ashing method. At the same biomass addition ratio, the ash sintering temperature of the blend with the wheat straw addition was lower than that with the pine sawdust addition, because the wheat straw had a higher K and Cl content but lower Ca than the pine sawdust. The EDS and XRD analyses confirmed that the ashes of coal/wheat straw blends contained more K-bearing minerals, while the ashes of the coal/pine sawdust contained more Ca and K-bearing minerals. Both Ca and K-bearing minerals reacted with other minerals in the ash to form low temperature eutectics, leading to the reduction of sintering temperatures of the coal and biomass blends. However, the melting points of the K-containing minerals are higher than the Ca-containing minerals, therefore, the sintering temperatures of ash with the wheat straw addition were lower than those with the pine sawdust addition.